Monitoring mortality in Pelotas birth cohort from 1982 to 2006, Southern Brazil - Horta, Bernardo L (2008)
OBJECTIVE: To assess mortality in a birth cohort followed between 1982 and 2006 and its associated factors. METHODS: In 1982, all of the 5914 children born in hospitals in the city of Pelotas, Southern Brazil, were identified and followed up prospectively. Between 1982 and 1987, deaths were identified through regular visits to hospitals, cemeteries and death registries. As of 1987, death data were obtained through the Mortality Information System. The studied variables were: gender, color of mother, mother's schooling rate, family income, weight at birth, weight and height per age. Poisson regression was used to estimate the relative mortality risk. RESULTS: Between 1982 and 2006 there were 288 deaths. The infant mortality coefficient was 36 deaths/1 000 live births; and in the age brackets 1-4, years, 5-14 years and 15-24 years the mortality rates were, respectively, 14.4, 4.1 and 5.4 deaths for every 1 000 live births at the beginning of the period. In all age brackets, mortality was higher for individuals from low-income families, with a relative risk of 2.89 (95% CI: 2.08; 4.03) when comparing the first and third terciles after control for gender and skin color. Low weight at birth and height-for-age and weigh-for-height deficits were found to be associated to a higher mortality rate until age 4, but not after that age. CONCLUSIONS: The effects of social inequalities during childhood can be felt until the beginning of adult life, but birth weight and childhood nutritional status do not have a long-lasting effect on mortality rates for adolescents or young adults.